Guidance for improving nutrition-relevant development in West Africa - Casu, Laura; Uzhova, Irina; Diatta, Ampa Dogui; Dramé, Mariame; Verstraeten, Roosmarijn (International Food Policy Research Institute, 2021)
This provides guidance for improving nutrition-relevant in West Africa, drawn from a comprehensive review of nutrition-relevant policies in 16 countries: Benin, Burkina Faso, Cape Verde, Côte d’Ivoire, Gambia, Ghana, Guinea, Guinea-Bissau, Liberia, Mali, Mauritania, Niger, Nigeria, Senegal, Sierra Leone, and Togo.